Creating a Wiring Framework for Embedded GUI Programming Course - Kertész, Csaba Zoltán (IEEE, 2021)
This paper presents the results of implementing the Wiring unit for Embedded Wizard, which offers the possibility of using functions familiar from Arduino projects inside a high level GUI building and prototyping environment. The unit allows students for easier microcontroller interfacing of their embedded GUI applications, so they can focus on studying UI and UX design concepts and doing online or offline prototyping of their applications without the need for extensive hardware testing.During the development of the Wiring-like framework also a large-scale study was performed about the usage of the framework in Arduino projects. Almost 200,000 Arduino source code files were analyzed from public GitHub repositories, and the findings about the topmost used functions and libraries are also presented in the paper.
Keywords: embedded systems; GUI; Arduino; Embedded Wizard; online education; Arduino function usage